VISUALISASI DATA STATISTIK KOMODITAS PERKEBUNAN DURIAN DI KECAMATAN TANGSE BERBASIS QUANTUM GIS - Nardi, Masykur; Husaini; Iskandar, Dedy (Yayasan Sagita Akademia Maju, 2024)
Durian plant is a fruit plant that can be cultivated and is included in horticultural crops. Based on data from the Central Statistics Agency (2018) obtained through the National Socio-Economic Survey (SUSENAS) in 2019, the results showed that almost all Indonesian people, namely 97.29% consumed vegetables, then around 72.59% consumed fruit. Durian fruit is included in one of the indicators in the survey ranking eighth out of a total of ten fruit commodities surveyed by the public, this shows that the demand for and consumption of durian fruit in Indonesia is still quite high. In this regard, a Geographic Information System (GIS) for mapping durian plantation commodities will be built. With this geographic information system, the Plantation and Forestry Service of the Pidie district can manage field data more quickly and in good detail. The GIS creation above uses the QGIS application to create maps, then digitizes image data from the monitoring layer and analyzes spatial data and uses the Google Earth application to digitize coordinates. The objectives of this research are as follows: To make it easier for the government to manage field data quickly and in detail, then the relevant departments can record durian plantation land owners for distribution of assistance and selection of suppliers for business units that require materials from durian harvests.